A Case Report on Ankle Joint Pathology of Car Drivers and Passengers - Jacek Karski; Tomasz Karski; Katarzyna Karska; Jaroslaw Pyrc (New Horizons in Medicine and Medical Research Vol. 10, 2022)
The study described a new pathology syndrome of the ankle joint, the chronic distortion caused by rotation movement made during getting out the car. We treated in period of 16 years, 26 patients (n=26) with chronic insufficiency due to the distortion of the ankle joint leading to limitation of dorsal flexion of the foot and pain syndrome. The causes of the distortion of ankle joint appears in the moment of getting out from the car. The pain is caused by the joint’s instability. In our study, we explain this unique type of foot insufficiency – "instability of the ankle joint" and pain syndrome as a result of "permanent distortion of the ankle joint" – in nations with "right traffic regulations" - left leg by drivers and right leg by passengers.